Acquired Amegakaryocytic Thrombocytopenia with Glycoprotein IIb/IIIa Antibody in a Patient with Mantle Cell Lymphoma - Sato, Keijiro; Ueki, Toshimitsu; Tokutake, Takayoshi; Ueno, Mayumi; Ichikawa, Naoaki; Sumi, Masahiko; Kobayashi, Hikaru (Internal Medicine, 2025)
Acquired amegakaryocytic thrombocytopenia (AAMT) is a rare disorder characterized by thrombocytopenia, marked megakaryocytic hypoplasia, and preserved other-lineage hematopoiesis in the bone marrow. The etiology of AAMT remains poorly understood owing to its rarity. We encountered a diagnostically challenging case involving a 66-year-old man who showed severe thrombocytopenic bleeding with isolated megakaryocytic hypoplasia, elevated serum thrombopoietin levels, glycoprotein IIb/IIIa antibody positivity, and prolonged platelet transfusion refractoriness following mantle cell lymphoma (MCL). Treatment with corticosteroids and intravenous immunoglobulin was ineffective, while a combination of multiagent chemotherapy, including rituximab, was beneficial for both thrombocytopenia and MCL. Ultimately, the patient was diagnosed with AAMT and immune thrombocytopenia (ITP)-like platelet destruction. This case suggests that AAMT and ITP are non-exclusive and sometimes overlap as components of a broad spectrum of platelet-related autoimmune diseases.